Розгляд судом справ про оголошення фізичної особи померлою та встановлення юридичного факту смерті - Коваленко, О. О.; Kovalenko, O. O. (Право і безпека. - 2016. - № 1 (60). - С. 130–135, 2016)
Досліджено внесені до Цивільного процесуального кодексу України зміни, які пов’язані з порядком оголошення фізичної особи померлою та встановленням юридичного факту смерті. Проаналізовано окремі положення Цивільного та Цивільного процесуального кодексів України з метою виявити суперечності, що з’явились у цивільному процесуальному законодавстві після закріплення цих змін, і надати рекомендації з удосконалення чинного матеріального й процесуального законодавства України з урахуванням міжнародного досвіду та вимог актуальності й сучасності.

The author has studied the amendments made to the Civil and Procedural Code of Ukraine associated with the procedure of declaring an individual dead and establishment of the legal fact of death. The author has analyzed some provisions of the Civil, Civil and Procedural Codes of Ukraine to reveal the contradictions that emerged in the civil procedural law after the consolidation of these amendments and to provide recommendations for improvement of the current material and procedural legislation of Ukraine considering international experience and requirements of relevance and modernity. It is noted that the legislator defines three grounds for declaring the death of an individual, including: – sustainable condition of being a missing person (for 3 years); – an individual gone missing under circumstances threatening death or giving the reason to believe his death from a specific accident (for 6 months); – under the condition to assume an individual dead from an accident or other circumstances because of man-made emergencies and natural disasters (for 1 month after the conclusion of a special commission’s work, formed as a result of emergencies of technogenic and natural character). It is concluded that there is a conflict of two reasons for declaring the death of an individual within one norm – determining the terms of declaring the death of an individual.

Исследованы внесённые в Гражданский процессуальный кодекс Украины изменения, связанные с порядком объявления физического лица умершим и установлением юридического факта смерти. Проанализированы отдельные положения Гражданского и Гражданского процессуального кодексов Украины с целью выявить противоречия, появившиеся в гражданском процессуальном законодательстве после закрепления этих изменений, и дать рекомендации по усовершенствованию действующего материального и процессуального законодательства Украины с учётом международного опыта и требований актуальности и современности.
The court hearings of the cases on declaration of death of an individual and establishment of the legal fact of death
Рассмотрение судом дел об объявлении физического лица умершим и установлении юридического факта смерти
Коваленко, О. О. Розгляд судом справ про оголошення фізичної особи померлою та встановлення юридичного факту смерті / О. О. Коваленко // Право і безпека. - 2016. - № 1 (60). - С. 130–135.
Kovalenko, O.O. (2016), “The court hearings of the cases on declaration of death of an individual and establishment of the legal fact of death” [“Rozhliad sudom sprav pro oholoshennia fizychnoi osoby pomerloiu ta vstanovlennia yurydychnoho faktu smerti”], Pravo i Bezpeka, No. 1, pp. 130–135.
Keywords: Цивільно-процесуальне право. Civil and Procedure Law. Гражданское процессуальное право; Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; фізична особа; оголошення особи померлою; нещасний випадок; надзвичайна ситуація; встановлення факту смерті; individual; declaration of death; accident; emergency; establishing the fact of death; физическое лицо; объявление лица умершим; несчастный случай; чрезвычайная ситуация; установление факта смерти